The Impact of the Fourth Edition of the WHO Classification of Lung Tumours on Histological Classification of Resected Pulmonary NSCCs. Issue 6 (June 2016) - Micke, Patrick; Mattsson, Johanna Sofia Margareta; Djureinovic, Dijana; Nodin, Björn; Jirström, Karin; Tran, Lena; Jönsson, Per; Planck, Maria; Botling, Johan; Brunnström, Hans
ABSTRACT : Introduction: : Histopathological classification of lung cancer is of central importance in the diagnostic routine, and it guides therapy in most patients. The fourth edition of the World Health Organization (WHO) Classification of Lung Tumours was recently published and includes changes to the diagnostic procedure for non–small cell carcinomas (NSCCs), with more emphasis on immunohistochemical (IHC) staining. Methods: : A total of 656 unselective cases of resected pulmonary NSCC were diagnosed according to the 2004 WHO classification. After IHC staining with cytokeratin 5, p40, p63, thyroid transcription factor 1 (clones 8G7G3/1 and SPT24), and napsin A, the diagnoses were revised in accordance with the new fourth edition of the WHO classification. Results: : Reclassification led to a new histological annotation in 36 of the 656 cases (5%). Most notable was the decrease in cases previously classified as large cell carcinomas (56 versus 12 cases). This was partially due to the exclusion of 21 neuroendocrine tumors from this group, with 20 cases ascribed to the adenocarcinoma group on the basis of IHC markers. Only seven cases of adenocarcinoma or squamous cell carcinoma were reclassified after the addition of IHC staining. There was a substantial overlap in staining properties between different markers of squamous and adenocarcinomatous differentiation, respectively, but in 17 to 31 cases (3%–5%), the diagnosis depended on the choice of markers. Conclusions: : The fourth edition of the WHO Classification of Lung Tumours leads to changes in histological type in 5% of resected NSCCs. The incorporation of IHC staining into NSCC diagnostics demands awareness that the choice of ancillary stains has an effect on diagnosis.